Aging together : dementia, friendship, and flourishing communities - McFadden, Susan H.; McFadden, John T. (Book collections on Project MUSE., 2011)
"Never in human history have there been so many people entering old age -- roughly one-third of whom will experience some form of neurodegeneration as they age. This seismic demographic shift will force us all to rethink how we live and deal with our aging population. Susan H. McFadden and John T. McFadden propose a radical reconstruction of our societal understanding of old age. Rather than categorize elders based on their respective cognitive consciousness, the McFaddens contend that the only humanistic, supportive, and realistic approach is to find new ways to honor and recognize the dignity, worth, and personhood of those journeying into dementia. Doing so, they argue, counters the common view of dementia as a personal tragedy shared only by close family members and replaces it with the understanding that we are all living with dementia as the baby boomers age, early screening becomes more common, and a cure remains elusive. The McFaddens' inclusive vision calls for social institutions, especially faith communities, to search out and build supportive, ongoing friendships that offer hospitality to all persons, regardless of cognitive status. Drawing on medicine, social science, philosophy, and religion to provide a broad perspective on aging, Aging Together offers a vision of relationships filled with love, joy, and hope in the face of a condition that all too often elicits anxiety, hopelessness, and despair"--Provided by publisher.